Penilaian Alternatif pada Keterampilan Berbicara Bahasa Inggris di Sekolah Menengah Kejuruan Kota Pontianak - Lilis Listiyawati; Anggita Anggita; Riska Wahyuni; Heriyanto Heriyanto (Jurusan Akuntansi Politeknik Negeri Pontianak, 2021)
English speaking skill is an important communication skill and must be mastered by students to be able to interact actively, convey ideas and provide responses in both formal and informal situations. Alternative assessment provides benefits for students and teachers in improving students' speaking skill in English. This research focuses on an alternative assessment of English speaking skill in Vocational High Schools in Pontianak City, especially South Pontianak. The objectives of this research are (1) to determine problems related to the English speaking skill of vocational school students in South Pontianak, (2) to identify and analyze alternative assessments applied in overcoming the problems of English speaking skill of vocational school students in South Pontianak, and 3) to find a solution to the English speaking skill problems of vocational school students in South Pontianak by using alternative assessments. This research was a qualitative research, and data were collected from interviews with English teachers and documents analysis. Data were collected through interviews with English teachers at SMK in south Pontianak and analysis of related documents. The stages of data analysis include data reduction, display data, and conclusion drawing / verification. The results showed that the problems faced by students related to English speaking skill were limited ability of students caused by several factors, namely grammar, pronunciation, vocabulary and self-confidence. The alternative assessments that were applied include performance - assessment, peer - assessment and portfolio. The solutions taken were to involve students in providing assessments to other students and the teacher focuses on conveying information clearly and conveying the moral values that are learned without focusing too much on grammar. The suggestions that the researchers gave were in the form of matriculation for students in the early year of school, knowledge sharing between teachers, determining priority aspects of speaking that were assessed and implementing self-assessment as an additional form of alternative assessment that could motivate and encourage students to gradually improve their speaking skills in English.